1981
DOI: 10.1073/pnas.78.3.1629
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a second Escherichia coli groE gene whose product is necessary for bacteriophage morphogenesis.

Abstract: Previous-work has uncovered the existence of an Escherichia coli locus, groE, that is essential for bacterial growth,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
82
0
5

Year Published

1989
1989
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(95 citation statements)
references
References 21 publications
8
82
0
5
Order By: Relevance
“…The results identified the formation of all the stable complexes of GroEL with the bound components, and the bands in each lane appear at MM positions of the expected components. The band of GroES subunit appeared above the lysozyme band at the position corresponding to an apparent MM of 15 kDa but not 10 kDa as also noted by Tilly et al (25). The order of addition of the ligands had no effect on the formation of all the ternary complexes.…”
Section: Identification Of Complexes Of Groel With Different Ligands-bysupporting
confidence: 76%
“…The results identified the formation of all the stable complexes of GroEL with the bound components, and the bands in each lane appear at MM positions of the expected components. The band of GroES subunit appeared above the lysozyme band at the position corresponding to an apparent MM of 15 kDa but not 10 kDa as also noted by Tilly et al (25). The order of addition of the ligands had no effect on the formation of all the ternary complexes.…”
Section: Identification Of Complexes Of Groel With Different Ligands-bysupporting
confidence: 76%
“…It was shown that the glycine residues are needed to ensure flexibility required for the mobile loop ␤ hairpin conformation (15,16). However, bacteria containing GroES with mutations in Gly-24 were viable, suggesting that perhaps one glycine at this position is sufficient for function of GroES (16,27,28). Consistent with these reports, the GroES mutant G24A was equally as active as wild type GroES at room temperature with a similar EC 50 , and was able to inhibit GroEL ATPase (Table 1; Fig.…”
Section: Purification and Structural Properties Of Wild Type Andmentioning
confidence: 99%
“…Certain unfolded or partially folded polypeptides bind to GroEL, a double-toroid, tetradecameric protein composed of 58-kDa subunits arranged with 7-fold symmetry (3)(4)(5). GroES, made up of 10.5-kDa subunits arranged in 7-fold symmetry (6,7), binds to GroEL, thus stabilizing a conformational change that doubles the substrate-containing cavity of GroEL and promoting the release of the substrate into the cavity (8,9). The amount of time the substrate spends in the cavity depends on the rate of ATP hydrolysis in the GroEL cis ring and the release of GroES (10,11).…”
mentioning
confidence: 99%